Ofelizm - Czeczot, Katarzyna (Instytut Badań Literackich Polskiej Akademii Nauk, 2024)
‘Ophelism’ is not a concept parallel to ‘Hamletism’. It should be defined as a visual code. It emerged at the turn of theeighteenth century, independently from theatre tradition, because it had little to do with the female protagonist herself,being based not on the scenes with Ophelia participating, but on the depictions of her death. It has been accepted as common knowledge thatthose images of a young female body immersed in water and/or flowers embody misogynist imaginings, framing femininity as madness, untamed sexuality or belonging to the realm of nature. The book Ophelism. Romantic Reappropriations, Feminist Interventions stemmed from the conviction that, from the beginning up until now, Ophelism comprised several threads. The studies presented in this book focus on the representations of female (at times, effeminate) body, where the themes of water and flowers serve to unsettle traditional narratives, questioning gender dualism, the opposition between nature and culture, and hierarchical order. Analyses of selected texts, paintings and performances provide an alternative history of Ophelism here, in which the stakes are the questions of its subversive potential.